Optimalisasi Struktur Modal: Profitabilitas Memediasi Nilai Perusahaan pada Sub Sektor Batubara Periode 2019-2023 - Rosyid Rosyid; Srie Nuning Mulatsih; Budiastuti Fatkar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In this study, it is investigated how the optimal capital structure can impact the value characteristics of coal companies and whether the capital structure will have an impact on firm value through the mediating variable of profitability. The data collection technique used panel data from leading coal companies and applied regression analysis method to test the influence between independent variables, mediating variables, and dependent variables. The research findings show that there is a significant influence between capital structure and probability characteristics, with the mediating variable of profitability playing a significant role. The findings can provide valuable insights for coal company management in adapting its capital structure.